Superhydrophobic property of cement mortar with polydimethylsiloxane modifier and a rough surface - Siyu Yu; Li Li; Chao Zhou; Song Lan (Case Studies in Construction Materials)
Hydrophobic modification has been widely used to prepare waterproof concrete, but reduces mechanical stability of the concrete, thereby limiting its applications in engineering. Currently, ultra-high performance concrete (UHPC) is the focus of research, but UHPC modified by hydrophobic agents is rarely reported. In this paper, different amounts of polydimethylsiloxane (PDMS) was used as modifier to produce hydrophobic UHPC (HUHPC). Spraying of powders ground from HUHPC and covering of a copper mesh were used to construct surficial texture of the UHPC and the HUHPC samples, respectively. The surface of UHPC sample, after sprayed by HUHPC powders with 9 % PDMS modifier, is superhydrophobic, exhibiting a contact angle of 151° and a sliding angle of 9°. While the surface of HUHPC sample, covered by the copper mesh, is hydrophobic effect with a maximum value of contact angle at 142°. Changes in pore structure of PDMS-modified UHPC were investigated to provide insight into the deterioration of the mechanical properties of UHPC. Hydrophobic modified HUHPC has sufficient mechanical properties to meet engineering requirements. Molecular dynamics simulations validates the mechanism of superhydrophobicity. The HUHPC sample with 9 % PDMS has an adhesion force of 0.0045 g for water on its surface and exhibits both hydrophobicity and self-cleaning. It is demonstrated that waste powders of these PDMS modified specimens are potential for recycling in applications of superhydrophobic coatings and oil-water separation.